Future of Precision Agriculture in India using Machine learning and Artificial Intelligence - Mokaya, Victor (International Journal of Computer Sciences and Engineering, 2019)
The changes in weather and climate conditions have always affected crop cultivation, farming and animal breeding. Measures put in place sometimes fail. Information and cognitive technologies are innovative techniques that can be leveraged to combat these changes by applying precision agriculture. In this paper discussion is on future of precision agriculture which has been proven to work in other countries using machine learning & artificial intelligence. The scope of utilization is focused on medium and large scale farmers with an aim to point out the advantages and disadvantages of the techniques. Previously there has been a slow growth in this sector but from the year 2016 onwards many start ups have been emerging which are yielding high investments. These cognitive technologies have been applied in advanced countries and have resulted in increased yield, growth in GDP, low mortality rates and improved living standards. The same can be applied locally to boost production in the agricultural sector.